2018
DOI: 10.1002/erv.2652
|View full text |Cite
|
Sign up to set email alerts
|

Food addiction distinguishes an overweight phenotype that can be reversed by low calorie diet

Abstract: Similarities in neural activation patterns in obese and substance‐dependent subjects led to the food addiction concept, but studies exploiting this issue for obesity stratification are missing. We assessed brain activation in response to food cues using 18F‐2‐fluoro‐2‐deoxy‐glucose‐PET in 36 overweight women, stratified by low or high food addiction groups according to the Yale Food Addiction Scale (YFAS). Assessments were repeated after a 3‐month diet. We found greater activation in thalamus, hypothalamus, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…Biological evidence suggests that the salt, sugars and fats contained within such highly palatable foods may have addictive potential via activating dopamine reward systems in the brain (2) . To this end, several different variables that may indicate the molecular, cellular and systems-level mechanisms (18) , reward mechanisms (19)(20)(21)(22)(23) , specific components of food (17,24,25) or diagnostic criteria for substance dependence in relation to eating behaviours (26)(27)(28) as an addiction have been recently examined. The alternative contention has focused on eating behaviours, rather than food.…”
Section: Current State Of Research On Food Addictionmentioning
confidence: 99%
“…Biological evidence suggests that the salt, sugars and fats contained within such highly palatable foods may have addictive potential via activating dopamine reward systems in the brain (2) . To this end, several different variables that may indicate the molecular, cellular and systems-level mechanisms (18) , reward mechanisms (19)(20)(21)(22)(23) , specific components of food (17,24,25) or diagnostic criteria for substance dependence in relation to eating behaviours (26)(27)(28) as an addiction have been recently examined. The alternative contention has focused on eating behaviours, rather than food.…”
Section: Current State Of Research On Food Addictionmentioning
confidence: 99%
“…Although some authors found that FA may act as a predictor of less weight loss after a low‐calorie dietetic intervention (Guerrero Pérez et al, ), others have shown that the presence of FA before surgery was not associated with presurgical body mass index (BMI) neither postoperative weight loss (Ivezaj, Wiedemann, & Grilo, ). Furthermore, some studies have revealed that the weight loss induced by a low‐calorie diet (Guzzardi et al, ) or by bariatric surgery (Murray, Tweardy, Geliebter, & Avena, ; Pepino, Stein, Eagon and Klein, 2014; Sevinçer, Konuk, Bozkurt and Coşkun, 2016) induced remission of FA symptoms and improved several dietary behaviours associated with FA.…”
Section: Introductionmentioning
confidence: 99%
“…Panel B illustrates the effect of exposure to maternal obesity, resulting in a hypermetabolic brain response to isoglycemic insulin stimulation (solid line) in very early life (70), and mild brain hypermetabolism in fasting conditions (dashed lines) (92). Panel C shows the progressive increase of brain glucose uptake in response to food presentation in inhibitory control regions (open circles) and in reward related regions (closed circles) from normal weight women to women with obesity without and with food addiction (62, 64) in adult age. In panel D, a progressive increment in fasting brain glucose uptake from normal weight mice with Alzheimer’s disease (AD, blue line), to normal weight mice without AD (green line), obese mice with AD (purple line) and obese mice without AD (red line) is shown (69).…”
Section: Homeostatic Regulation Of Brain Glucose Metabolism In Obesitymentioning
confidence: 99%
“…We have recently hypothesized that the magnitude and regional distribution of hedonic food responses might differ between similarly obese individuals, opening the opportunity for mechanistic based stratification, and personalized management of obese patients. In order to prove this concept, we studied two groups of obese women, who had similar metabolic profile and BMI, but different severity of food addiction symptoms, as based on the DMS Yale Food Addiction Scale (64). Compared to women with few symptoms, the more severely affected group showed greater brain metabolic activation in response to palatable versus neutral food cues, especially in reward-related regions, and less in inhibitory control regions (64).…”
Section: Hedonic Regulation Of Brain Glucose Metabolism In Obesitymentioning
confidence: 99%
See 1 more Smart Citation